2019
DOI: 10.12659/msm.917356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodontitis and Toothbrushing Frequency on Obesity Onset: A Cohort Study

Abstract: Background: The interplay between obesity and periodontitis has been widely examined. While obesity was reported as a risk factor for periodontitis, the inverse relationship is still little explored. Therefore, we aimed to determine whether periodontitis and toothbrushing frequency affect the onset of obesity. Material/Methods: This cohort study included 1619 employees of a business enterprise headquartered in Tokyo, who in 2002 and 2006 underwent in prescribed annual health checks, both general and dental-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Even if those with dry mouth due to diabetes were excluded, dry mouth was found to be more common in middle-aged and older people. For an increased risk of obesity, in the current study, our findings on oral self-care habits in men and women were supported by results from previous studies [14,35], but we might not have found significant associations with oral hygiene. Surprisingly, a variety of OHIs and a series of oral health questions (e.g., our 15 questions) including "tooth brushing frequency" have not been examined in relation to risks of obesity, diabetes, cardiovascular diseases, and hypertension in many previous studies in Japan and American-European countries.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even if those with dry mouth due to diabetes were excluded, dry mouth was found to be more common in middle-aged and older people. For an increased risk of obesity, in the current study, our findings on oral self-care habits in men and women were supported by results from previous studies [14,35], but we might not have found significant associations with oral hygiene. Surprisingly, a variety of OHIs and a series of oral health questions (e.g., our 15 questions) including "tooth brushing frequency" have not been examined in relation to risks of obesity, diabetes, cardiovascular diseases, and hypertension in many previous studies in Japan and American-European countries.…”
Section: Discussionsupporting
confidence: 81%
“…Multivariable adjusted logistic regression analysis was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for obesity, compared with each 15 question on oral health (good as "reference") and each five OHI (the lowest tertile as "reference"). With reference to previous studies [6,14,31], the potential confounding factors were applied as follows: age (years), physical activity (METs‧h/day), total energy intake (kcal/ day), and tooth number (n) as continuous variables, and current smoker (no/yes = 0 / 1), current habitual drinker (no/yes = 0 / 1), snacking (none/sometimes/everyday = 1 / 2 / 3), education level (< 12 / 12 / > 12 years = 1 / 2 / 3), medications [no/yes = 0 / 1 for diabetes, dyslipidemia, hypertension, angina myocardial infarction, and cerebral stroke, respectively] and tooth/gum conditions [no/ sometimes/yes = 1 / 2 / 3 for tooth pain, gum bleeding, and gum swelling, respectively] as categorical variables.…”
Section: Statistical Analysesmentioning
confidence: 95%
“…There are few studies addressing the associations between oral health and the risk of obesity, especially in children. A cohort study in Japanese adults found that brushing teeth frequently (>3 times/day) may reduce the risk of obesity (OR: 0.49, 95% CI: 0.28–0.85) ( 36 ). Our study expands previous findings and showed that unhealthy toothbrushing habit was also a risk factor for overweight/obesity in students.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Morita et al reported a significant association between toothbrushing frequency (≥ three times / day) and onset of obesity in a 4-year cohort study of individuals who were not obese (BMI < 25kg / m 2 ) at baseline (15). They concluded that people who brushed their teeth frequently (i.e., had good toothbrushing practices) are at low risk of becoming obese.…”
Section: Discussionmentioning
confidence: 99%